Change in the physicalmechanical and decorative properties of labradorite under thermal exposure - Korobiichuk, Valentyn; Shlapak, Volodymyr; Sobolevskyi, Ruslan; Sydorov, Oleksandr; Shaidetska, Liubov (Eastern-European Journal of Enterprise Technologies, 2019)
We have experimentally investigated samples from the four fields of coarse-grained labradorite, which is extracted in Ukraine. The samples of labradorite were tested at high temperatures of 200, 300, 400, 500, 600, 700, 800, 900 °С. Red spots at the surface of samples is the result of oxidation of the metal Fe2+: at different fields of labradorite they cover a different area of the sample’s surface of natural stone: it ranges from 39 to 60 %. An analysis of the polished labradorite surface after heating revealed that red inclusions are evenly distributed over the surface of labradorite samples. Oxidation of minerals, which is visually observed on all the samples of labradorite, starts at a temperature of 300 °С. One of the features in the research described in this paper is the application of digital image processing in order to quantitatively assess the Fe oxidation area (red spots) at the polished surface of labradorite samples. To a temperature of 500‒600 °С, there is a gradual increase in the oxidized area of the samples’ surface. At temperatures above 700 °С, there is a sharp increase in the oxidized area at the samples’ surface. In general, the oxidized spots of metals cover between 40 to 60 % of the surface of labradorite samples. When heated, the labradorite samples become 50 % brighter than the original value for indicator L in the color system Lab. A decrease in the velocity of ultrasonic wave propagation in labradorite samples occurs evenly, without surges. The reason for a decrease in the ultrasonic wave velocity is the formation of defects and cracks in labradorite samples due to an uneven thermal expansion of minerals. At a temperature of 700 °С ° or higher, there is a decrease in the velocity of ultrasound wave propagation in the samples of natural stone. At heating, there is a decrease in the indicators for gloss in all labradorite samples. In general, when labradorite was heated up to 900 °С, the samples from the Ocheretyansky deposit lost 11.21 % of their gloss, from the Neviryvsky deposit ‒ 4.03 %, from the Osnikivske deposit ‒ 33.57 %, from the Katerinovsky deposit ‒ 15.3 %.